КОМУНІКАТИВНА ВЗАЄМОДІЯ ЯК СКЛАДОВА ПРОФЕСІЙНОЇ МАЙСТЕРНОСТІ МАЙБУТНЬОГО ВЧИТЕЛЯ ТЕХНОЛОГІЇ (Педагогіка вищої та середньої школи, 2008)
The article is dedicated to the problem of forming the professionally significant communicative skills of would-be Handicraft teachers in the conditions of the introduction the educational field “Technology ”.